2014 IEEE 26th International Conference on Tools With Artificial Intelligence 2014
DOI: 10.1109/ictai.2014.70
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis: Towards a Tool for Analysing Real-Time Students Feedback

Abstract: Abstract-Students' real-time feedback has numerous advantages in education, however, analysing feedback while teaching is both stressful and time consuming. To address this problem, we propose to analyse feedback automatically using sentiment analysis. Sentiment analysis is domain dependent and although it has been applied to the educational domain before, it has not been previously used for real-time feedback. To find the best model for automatic analysis we look at four aspects: preprocessing, features, mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 8 publications
1
48
0
3
Order By: Relevance
“…This finding is consistent with a number of recent studies discussing students' Sentiment analysis (e.g. [9], [8] and [14]).…”
Section: Experiments Results and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with a number of recent studies discussing students' Sentiment analysis (e.g. [9], [8] and [14]).…”
Section: Experiments Results and Discussionsupporting
confidence: 93%
“…Given the importance of obtaining real-time feedback from students to improve educational outcomes, we found that many previous studies have tried to analyse student feedback and extract student sentiment using different techniques and tools. In [8], machine learning techniques, preprocessing levels and the use of neutral class were used to analyse real-time student feedback. It was found that preprocessing the data improved accuracy by 20%.…”
Section: Natural Language Processingmentioning
confidence: 99%
“…Most approaches in the sentiment analysis area focus on polarity or opinion classification into positive or negative classes [8], [9], [10]; some researchers also include a neutral class [11], [12]. Other classification tasks focus on subjectivity vs. objectivity [13], on predicting categories of emotions (e.g.…”
Section: Related Studiesmentioning
confidence: 99%
“…The research in this area has been applied to a variety of data sources, such as movie reviews [10], product reviews [17], [18], Facebook data [11] and micro-blog data [12], [19]. In this research reported in this paper we use movie reviews data.…”
Section: Related Studiesmentioning
confidence: 99%
“…positive/negative/neutral, and (b) the presence in the feedback of particular emotions related to learning, e.g. excitement and boredom [2], [3]. We also created six visualisations to present the results to the lecturers.…”
Section: Introductionmentioning
confidence: 99%